Media Elegant Teleprompter sebagai Alternatif Media Pembelajaran Membaca Teks Berita Siswa Kls VIII MTs Nurul Yaqin Proppo - In’am,; Alatas, Mochamad Arifin (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2023)
Obstacles in reading news are the demand to read aloud and the speed of the eye in maintaining focus. This research is to describe the use of the elegant Teleprompter as an alternative learning medium for students to read news texts. The research uses descriptive qualitative methods. Data collection methods in this research used observation, interviews and documentation. The results of this research are that the use of elegant Teleprompter as an alternative learning media has several stages. These stages include 1. Manufacturing process/steps consisting of how to install, how to use and how to create scripts 2. Implementation, which consists of explaining what Elegant Teleprompter is, practicing and giving directions and 3. Evaluation consisting of suitability for learning media, weaknesses and lack.